2022
DOI: 10.1155/2022/8712424
|View full text |Cite
|
Sign up to set email alerts
|

Progression of COVID-19 in a Patient on Anti-CD20 Antibody Treatment: Case Report and Literature Review

Abstract: Accumulating evidence suggests that anti-CD20 treatments are associated with a more severe course of COVID-19. We present the case of a 72-year-old woman treated with the B-cell-depleting anti-CD20 antibody rituximab for seropositive rheumatoid arthritis with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection causing a clinical relapse more than 4 weeks after the first manifestation. Persistently positive reverse transcription polymerase chain reaction (RT-PCR) results along with a drop in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Since the beginning of the pandemic, some cases of COVID-19 in patients treated with anti-CD20 monoclonal antibodies (antyCD20mAB) due to haematological illnesses, have been described [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The majority of those patients received rituximab.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the beginning of the pandemic, some cases of COVID-19 in patients treated with anti-CD20 monoclonal antibodies (antyCD20mAB) due to haematological illnesses, have been described [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The majority of those patients received rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients, the course of COVID-19 was mild at the beginning and they required only observation but after a couple of weeks, they presented to the hospital with symptoms such as elevated body temperature, dyspnoea, and dry cough [ 3 , 7 , 8 , 11 , 12 , 13 ]. Some patients developed respiratory failure during the disease course [ 3 , 4 , 5 , 6 , 7 , 8 , 10 , 11 , 12 , 14 ]. Only a few died because of severe COVID-19 courses [ 6 , 9 , 10 , 11 , 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several public health bureaus, including the National Health Service in the United Kingdom and the National Institutes of Health in the United States, define patients treated with B‐cell depletion therapy as susceptible to the highest risk or requiring prioritized treatment 8,9 . Prior observational studies have shown an association between patients treated with B‐cell depletion therapy and prolonged and severe COVID‐19 infection; some of these patients experienced several months of COVID‐19 infections 10‐12 . This is partly because such patients did not develop detectable SARS‐CoV‐2 antibodies even after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…While initial studies suggested a protective effect for anti-CD20 treatment in COVID-19 infection [ 1 ] , it is now well established that COVID-19 patients treated with anti-CD20 shed the virus for longer periods and develop severe disease in higher proportions [ 2 ] . Case reports written before the emergence of B1.1.529 (Omicron) described an atypical disease course with persistent symptoms for weeks and relapse shortly after resolution of initial symptoms [ 3 , 4 ] . Here we explore four cases of COVID-19 related lung disease in anti-CD20 treated patients, presenting during the Omicron wave in Israel.…”
Section: Introductionmentioning
confidence: 99%